Study the effect of mifepristone on fibroid and uterine volume - Seher, Umbreen; Chauhan, Nidhi; Mangla, Mishu (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Fibroid is the most common benign tumour of the uterus affecting 20% of women of reproductive age group and is the most common indication for hysterectomy accounting for about 40% of all hysterectomies in premenopausal women. This study was undertaken to study the effect of Mifepristone, which is a progesterone receptor modulator with antagonistic action, on fibroid and uterine volume. Methods: The study was conducted in the Department of Obstetrics and Gynaecology, Himalayan Institute of Medical Sciences, Swami Ram Nagar, Dehradun over a period of 12 months. A total of 40 patients were included in the study. Results: Mean baseline fibroid volume decreased by 49.17% at 1 month and by 77.4% and 3months of treatment with Mifepristone. Mean baseline uterine volume decreased by 34.13% at 1 month, and further reduction by 58.3% at the end of treatment. Conclusions: The study shows that there is a significant reduction in fibroid and uterine volume in patients treated with mifepristone.